Effect of enlarged cage on production in foxes - Hannu. T. Korhonen; Orjala, Hanna (Nordic Association of Agricultural Scientists, 2009)
The aim was to find out the effect of higher and wider cage on production in farmed blue fox. Three different cage setups formed the three experimental groups: 1) control group in standard cage; 2) high cage, walls heightened close to the roof of shed; 3) wide cage, cage built to fit between the supporting structures of the shed. The weight development was normal in all groups. Capture test showed that the fox was caught ca. 3 seconds faster from the standard cage than from the high cage. It took longest to catch a fox from the wide cage. The time it took to catch a fox increased in all groups as the foxes grew. At pelting, the capture time was longest in a high cage and shortest in a standard cage.. The foxes remained healthy throughout the study and the results of small blood picture indicated of good general health in all groups. Right and left adrenal glands were heaviest in foxes with high cages. Raising the roof of the cage succeeded without difficulties. The door is traditionally situated on the roof of a cage which now had to be displaced on the front wall of the cage. The door needs more developing. When foxes grew, a second person was needed to hold the door when catching a fox, which prolonged the time needed to catch a fox. The two doors in the wide cage were situated on both ends of the cage, thereby complicating the capture. Only one door situated in the middle of the cage could ease the capture. The animal grew well, remained healthy and produced a good fur, so high cage seems to be suited for housing foxes. High cage also seamed to be the less stressful cage setup of all three. Because of the high roof, foxes are able to sit on the self and the roof does not wear down the fur on the back. Moreover, a great height makes it possible to attach another self on the wall.
Keywords: Ko; sinikettu; turkiseläimet; turkistuotanto; häkit; hyvinvointi; furbearing animals; cages; animal welfare; blue fox; fur animals; cage size; production result; fur production